Spatial and temporal aspects of cellular calcium signals: 'elementary' signals and waves - Parker, Ian (Henry Stewart Talks, 2007)
Calcium as a life and death cellular messenger, Sequestration and liberation of calcium from the endoplasmic reticulum, Calcium release through inositol trisphosphate receptors and modulation by calcium, Optical techniques to visualize and stimulate intracellular calcium signals, 'Elementary' calcium signals through single channels and clusters of channels, Generation of periodic calcium waves by stochastic elementary events, Modulation of calcium signals by calcium binding proteins, The hierarchical organization of cellular calcium signals
Archived at 2021/02/25